Transcranial Doppler Use in Non-traumatic Critically Ill Children: A Multicentre Descriptive Study - Rollet-Cohen, Virginie; Sachs, Philippe; Léger, Pierre-Louis; Merchaoui, Zied; Rambaud, Jérôme; Berteloot, Laureline; Kossorotoff, Manoëlle; Mortamet, Guillaume; Dauger, Stéphane; Tissieres, Pierre; Renolleau, Sylvain; Oualha, Mehdi (Frontiers in Pediatrics, 2021)
Abstract Background: The use and perceived value of transcranial Doppler (TCD) scope in paediatric critical care medicine has not been extensively documented. Objective: To describe the use of TCD to assess non-traumatic brain injury in patients admitted to four paediatric intensive care units (PICUs) in France. Methods: We prospectively included all children (aged under 18) assessed with inpatient TCD between November 2014 and October 2015 at one of the four PICUs. The physicians completed a questionnaire within four hours of performing TCD. Results: 152 children were included. The primary diagnosis was neurological disease in 106 patients (70%), including post ischemic-anoxic brain insult (n=42, 28%), status epilepticus (n=19, 13%), and central nervous system infection/inflammation (n=15, 10%). TCD was the first-line neuromonitoring assessment in 110 patients (72%) and was performed within 24 hours of admission in 112 patients (74%). The most common indications for TCD were the routine monitoring of neurological disorders (n=85, 56%) and the detection of asymptomatic neurological disorders (n=37, 24). Concordance between the operator’s interpretation of TCD and the published normative values was observed for 21 of the 75 (28%) TCD abnormal findings according to the published normative values. The physicians considered that TCD was of value for the ongoing clinical management of 131 (86%) of the 152 patients. Conclusion: TCD is commonly used in French PICUs and tends to be performed early after admission on patients with a broad range of diseases. The physicians reported that the TCD findings often helped their clinical decision making. In view of the subjectivity of bedside interpretation, true TCD contribution to clinical care remains to be determined. Objective studies of the impact of TCD on patient management and clinical outcomes are therefore warranted.